MRI Evaluation of Lymphatic Abnormalities in the Neck and Thorax after Fontan Surgery: Relationship with Outcome - Biko, David M; DeWitt, Aaron G; Pinto, Erin M; Morrison, Rodney E; Johnstone, Jordan A; Griffis, Heather; O'Byrne, Michael L; Fogel, Mark A; Harris, Matthew A; Partington, Sara L; Whitehead, Kevin K; Saul, David; et al. (Radiology, 2019)
Background The Fontan operation is performed for surgical palliation of single ventricle physiology. This operation is usually preceded by a superior cavopulmonary connection (SCPC); lymphatic abnormalities after SCPC may be demonstrated at MRI and prior to the Fontan operation. Purpose To determine if the degree of neck and thoracic lymphatic abnormalities at T2-weighted MRI in patients after superior cavopulmonary connection (SCPC) correlated with surgical outcomes from the Fontan procedure. Materials and Methods Patients for whom SCPC was performed for palliation of single ventricle disease who underwent chest MRI between July 2012 and May 2015 at a single institution were retrospectively reviewed. T2-weighted images were scored as lymphatic type 1 (little or no T2 mediastinal and supraclavicular signal) to type 4 (T2 signal into both the mediastinum and the lung parenchyma). Fontan takedown, duration of post-Fontan hospitalization and pleural effusion, postoperative plastic bronchitis, need for transplant, and mortality were tabulated. The relationship between lymphatic type and clinical outcomes was evaluated by using analysis of variance (ANOVA), the Kruskal-Wallis H test, and the Fisher exact test. Results A total of 83 patients (mean age, 7.9 years ± 2.6) were evaluated. Among these 83 patients, 53 (64%) were classified with type 1 or 2 lymphatic abnormalities, 17 (20%) with type 3, and 12 (16%) with type 4. The rate of failure of Fontan completion was higher in patients with type 4 than in type 1 or 2 (54% vs 2%, respectively; = .004). Need for cardiac transplant (one of 13 [8%]) and death (three of 13 [23%]) occurred only in type 4. Median postoperative length of stay was longer for patients with type 4 than for those with types 1 or 2 (29 days vs 9 days, respectively; < .01). Conclusion Greater MRI-based severity of lymphatic abnormalities in patients prior to planned Fontan procedure was associated with failure of Fontan completion and longer postoperative stay. © RSNA, 2019